Environmental health and justice and the right to research: institutional review board denials of community-based chemical biomonitoring of breast milk. Issue 1 (December 2015) - Saxton, Dvera; Brown, Phil; Seguinot-Medina, Samarys; Eckstein, Lorraine; Carpenter, David; Miller, Pamela; Waghiyi, Vi
Abstract Recently, conflicts and challenges have emerged regarding environmental justice and research ethics for some indigenous communities. Alaska Community Action on Toxics (ACAT) responded to community requests for breast milk biomonitoring and conceived the Breast Milk Pilot Study (BMPS). Despite having community support and federal and private funding, the BMPS remains incomplete due to repeated disapprovals by the Alaska Area IRB (Institutional Review Board). In this commentary, we explore the consequences of years of IRB denials, in terms of health inequalities, environmental justice, and research ethics. We highlight the greater significance of this story with respect to research in Alaska Native communities, biomonitoring, and global toxics regulation. We offer suggestions to community-based researchers conducting biomonitoring projects on how to engage with IRBs in order to cultivate reflective, context-based research ethics that better consider the needs and concerns of communities.